THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND LEARNING ENVIRONMENT AT HOME WITH STUDENTS MATHEMATICS LEARNING OUTCOMES IN SMP NEGERI 2 SANDEN - Nur Hidayati; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Low self-confidence of students and the learning environment in the home students are still not conducive. This study aims to determine whether there is a positive and significant relationship between self-confidence and learning environment at home with student's mathematics learning outcomes of class VII SMP Negeri 2 Sanden Bantul second semester Academic Year 2015/2016. The population in this study were all students of class VIII SMP Negeri 2 Sanden  Bantul in second semester Academic Year 2015/2016 consists of 8 classes. Taken as a class VII A of the class sample with a purposive sampling technique that is input from the school. The technique of collecting data are questioner and tests. The research instrument testing use validity testing, different potency testing, and reliability testing. The analysis of prerequisite testing includes a normality test, independent test, and linearity testing. The analysis of the data uses to hypothesis testing using correlation analysis of moment product and multiple linear regression analysis. The results of the analysis of variance with a significant level of 5% and df = 25 show that there is a positive and significant correlation between self-confidence and learning environment at home with mathematics learning outcomes with  = 3,742705182 and  = 3,34 so . Multiple correlation coefficient (R) = 0,4800247482 and the linear regression equation  = -6,40017185 + 0,7301722041  + 0,4245148013 . Large relative contribution  = 54,551%  and  = 45,449% and the effective contribution  = 12,569% and  = 10,472%.